2019
DOI: 10.12659/msm.913602
|View full text |Cite
|
Sign up to set email alerts
|

Use of Genome-Scale Integrated Analysis to Identify Key Genes and Potential Molecular Mechanisms in Recurrence of Lower-Grade Brain Glioma

Abstract: Background The aim of this study was to identify gene signals for lower-grade glioma (LGG) and to assess their potential as recurrence biomarkers. Material/Methods An LGG-related mRNA sequencing dataset was downloaded from The Cancer Genome Atlas (TCGA) Informix. Multiple bioinformatics analysis methods were used to identify key genes and potential molecular mechanisms in recurrence of LGG. Results A total of 326 differentially-expressed gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…However, correlation between EZR gene expression in breast cancer and its correlation with patients’ survival is not fully understood. In recent years, with the development of cancer databases, more and more studies have been published in the aspects of deep data mining in the database through bioinformatics analysis . In the present work, we investigated the EZR gene expression in breast cancer, function enrichment and correlation with the prognosis through bioinformatics analysis and immunohistochemistry assay in order to provide a greater understanding of the EZR gene in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, correlation between EZR gene expression in breast cancer and its correlation with patients’ survival is not fully understood. In recent years, with the development of cancer databases, more and more studies have been published in the aspects of deep data mining in the database through bioinformatics analysis . In the present work, we investigated the EZR gene expression in breast cancer, function enrichment and correlation with the prognosis through bioinformatics analysis and immunohistochemistry assay in order to provide a greater understanding of the EZR gene in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Canty and Kadler found the relationship between collagen molecules and ECM. Similarly, Deng et al also found that the ECM‐receptor interaction pathway had a strong association with COL1A1, COL1A2, COL3A1, and so on. In addition, COL5A2 and COL3A1 collagen‐related genes have been identified that they participated in the remodeling of ECM .…”
Section: Discussionmentioning
confidence: 85%
“…And it has been proven that the expression level of COL1A2 in primary medulloblastoma was significantly elevated, higher than other medulloblastomas . COL3A1, encoding collagen type III alpha 1 chain, with high expression level was associated with glioma grades and it significantly increased in malignant glioma . Kuivaniemi and Tromp also have proven that COL3A1 gene participated in the progression of glioma.…”
Section: Discussionmentioning
confidence: 96%
“…However, the exact pathogenesis of glioma is still unclear [16,17]. In recent years, with the development of molecular biology technology, more and more evidence has shown that the occurrence and prognosis of glioma is related to the different expressed oncogenes and tumor suppressor genes [18][19][20].…”
Section: Discussionmentioning
confidence: 99%